2018
DOI: 10.1080/22201181.2018.1470810
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the isiZulu quality of recovery score

Abstract: Background: Recovery from anaesthesia and surgery is an important marker of the quality of perioperative care. One extensively validated score in assessing this is the Quality of Recovery-15 items (QoR-15) score. This study aimed to translate the QoR-15 score into isiZulu and validate both the original and translated version on an isiZulu speaking population. Methodology: A randomised quantitative observational study was performed testing the original and the translated version of the QoR-15 score. In a crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…27 An isiZulu translation of the QoR-15 has been validated. 21 This was used to supplement the English QoR-15 in cases where the patient preferred the isiZulu translation. Only 1 patient preferred to make use of this.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 An isiZulu translation of the QoR-15 has been validated. 21 This was used to supplement the English QoR-15 in cases where the patient preferred the isiZulu translation. Only 1 patient preferred to make use of this.…”
Section: Methodsmentioning
confidence: 99%
“…15 This is important in a resource-constrained South African setting, where studies on QoR are limited. 21,22…”
mentioning
confidence: 99%
“…This single-paged QoR-15 has been shown to be highly valid and reliable in patients who have undergone general surgery [ 4 ]. The QoR-15 has been validated and translated into many languages, including Danish, Portuguese, Chinese, Swedish, and IsiZulu [ 13 17 ]. All translated versions of QoR-15 had sufficient validity and reliability for evaluating the quality of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria were a known psychiatric disturbance precluding complete co-operation, cognitive impairment (known, or suspected and confirmed using a cognitive impairment test), [7] inability to understand English (self-professed), [6] unavailability for interview postoperatively (day cases, transferred to another hospital, intensive care unit admissions or life-threatening complications), age <18 years, surgical procedures conducted under sedation alone, or after-hours surgery. We also excluded patients with severe pre-existing medical conditions that would limit objective postoperative assessment (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…[5] The QoR scores have been translated and adapted for different social environments. [5] Recently, Sikhakhane et al [6] developed and validated an isiZulu translation of the QoR-15, demonstrating good validity of the isiZulu QoR-15 using psychometric methods. They also demonstrated that the original English QoR-15 is a valid tool for assessment of postoperative quality of recovery in a South African (SA) population.…”
Section: Researchmentioning
confidence: 99%